Edu-Connect: Transforming MSU Marawi Education through Social Media Networks - Abao, Jalal M.; Al-Mounaim, Tareeq A.; Pacasum, Hafida M.; Saidamen, Isoden; Viray, Marecon C.; Gogo, Hosnie B. (Assyfa Learning Journal, 2024)
The study investigates the role of Social Media Networks (SMN) as educational platforms at Mindanao State University, Marawi City, amidst the COVID-19 pandemic. It aims to answer three key questions: the common SNM used by students in online classes, their perceptions of SNM, and the effects of integrating SNM based on the Triple E framework (Engagement, Enhancement, Extension of learning objectives). A quantitative descriptive design with a validated survey questionnaire was employed, involving 104 students from the first semester of the 2021-2022 Academic Year. Data analysis included frequencies, percentages, weighted averages, and correlation tests. Results showed that Google, Messenger, and Facebook were the most frequently used SNM. About 85% of respondents had basic SNM knowledge, facilitating their adaptation to online learning. According to the Triple E framework, 78% demonstrated high engagement, 82% reported enhanced learning objectives, and 75% experienced expanded understanding through SNM. The study underscores the significance of integrating SNM into online learning. Recommendations include structured training on SNM usage, enhancing student-lecturer communication via SNM, limiting gadget use to combat digital fatigue (reported by 60% of students), innovating online learning methods, and optimizing SNM use by lecturers and staff for better material accessibility.